Faktor yang Mempengaruhi Capaian Pembelajaran Daring pada Mahasiswa Keperawatan - Hamdan Hariawan; Suratno Kaluku (Poltekkes Kemenkes Maluku, 2023)
The online learning process for nursing students during the Covid-19 pandemic provides a lot of room for educational actors to innovate. This online learning innovation is still considered good being implemented by educational actors even though the pandemic has been declared over. The purpose of this study was to determine the factors that influence the learning achievement of nursing students. This research was a descriptive analysis research with a cross sectional approach. Respondents in this study were 88 nursing students from the Maluku Health Polytechnic. The independent variables are the characteristics of the respondents which consist of gender, age, residential area, and last type of education. While the dependent variable is student learning outcomes. The results of this study show that gender, age, and the last type of education do not affect the results of online learning outcomes. Only residential area had an influence on online learning outcomes (p <0.05). The educational background in remote, border and island areas was usually known for various complex problems, one of which is the lack of facilities and infrastructure. The ability of nursing students to operate online learning media through devices is also inseparable from the learning outcomes.